The foundation of Islamic knowledge management practices - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah (Springer International Publishing, 2017)
This chapter is a brief description of the foundation of Islamic Knowledge Management (IKM), its functional characteristic and dimensional practices. The philosophy of knowledge is an established discipline in human civilization, especially in Islam. It is understandable that knowledge is a source of intellectual prosperity and development. Naturally, all aspects of human development such as social behavior, religiosity, political leadership, and business transaction flourishes with the application of efficient knowledge management. This understanding becomes evident especially within our contemporary globalization era and challenges. The issue of managing knowledge is vital in refining current developments, achievements, and performances, whether at individual or society level as well as the organizational level. Likewise, Islam regards knowledge management as a fundamental principle of conducts and practices in all affairs. It is embodied in a man as a society and cultural being with a divine trusteeship (amanah) as vicegerent (khilafah) and moral agents of God on earth. In short IKM is expected to fulfill the comprehensive understanding of science and philosophy structured by religion with a reference to the highest source of knowledge as presented by the Quranic verses and the Prophetic explanations.